Paddy Farmers’ Intention to Participate in Agriculture Takaful in Sri Lanka: A Case Study - Huraira, Rifas Abi; Seinulabdeen Nadhira Jahan (Talaa : Journal of Islamic Finance, 2021)
Paddy Farmers’ Intention to Participate in Agriculture Takaful in Sri Lanka: A case study Agriculture sector provides significant contribution to the national development thorugh economic growth. Nearly 70% of total population live in rural regions entirely or partially reliant on agriculture industry. Agriculture including paddy cultivation is the main source of income in Sri Lanka which is vulnerable sector by variety of hazards including flood, drought, heavy rain, diseases, and insect infestation. The study aims to measure paddy farmers' intention to participate in agriculture takaful. It was carried out to identify the factors using theory of planned behaviour (TPB) which consists of three aspects namely attitude, subjective norm and perceived behavioural control (PBC). Primary data were collected using questionnaire survey from 160 paddy farmers who were randomly selected from Sammanthurai. Statistical Package for Social Sciences (SPSS) was used to multiple regression analysis in order to determine the relationships between exogenous and endogenous variables. The results indicate that two factors namely attitude (p=0.000) and perceived behavioural control (p=0.000) have significant influence on paddy farmers' behavioural intention. Moreover, PBC is the highest predictor while subjective norm (p=0.311) has no impact on behavioural intention. This study contributes to takaful operators and takaful marketing department for strategic policies and decision making as well.